A PRESENTING OF UTERUS DIDELPHYS: A CASE REPORT - Vijaya Kumaran, Ghayathri; Saran (International Journal of Psychosocial Rehabilitation, 2020)
This is a case of double uterus reported by a student in Chennai, India. The patient is an 18-year-old female from Malaysia of Indian descent who is of normal health condition. Uterus didelphys (sometimes also uterus didelphys) represents a uterine malformation where the uterus is present as a paired organ as the embryonic genetic fusion of the mullerian ducts failed to occur. As a result, there is a double uterus with two separate cervix, and often a double vagina as well. Each uterus has a single horn linked to the ipsilateral fallopian tube that faces its ovary. The uterus is formed during embryogenesis by the fusion of the two paramesonephric ducts (also called mullerian ducts). This process usually fuses the two mullerian ducts into a single uterine body but fails to take place in these affected women who maintain their double mullerian systems. A didelphic uterus will have a double cervix and is usually associated with a double vagina. Causes for the failure to fuse are not known. Associated defects may affect the vagina, the renal system, and less commonly, the skeleton. The condition is less common than these other uterine malformations: arcuate uterus, septate uterus, and bicornuate uterus. It has been estimated to occur in 1/3,000 women. The findings of this case study are that the double uterus condition is not abnormal, and if the patient suffers acute pain, then the patient will need to seek medical help and may, in extreme cases, need corrective surgery. This is evidence that the double uterus condition is not abnormal and that it can be managed if detected. In most of the cases, unless a pelvis scan is done, this will not be detected.